2004
DOI: 10.1259/dmfr/26493631
|View full text |Cite
|
Sign up to set email alerts
|

Effect of beam energy and filtration on the signal-to-noise ratio of the Dexis intraoral X-ray detector

Abstract: For the Dexis intraoral radiographic imaging system, estimated SNR improved both with higher filtration and with lower kVp. The Dexis detector was capable of generating acceptable images of the step wedge at a wide range of kVp settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 9 publications
2
11
0
Order By: Relevance
“…Our results corresponded to another authors, as well. Kitagawa and Farman (2004) reported that the Signal-to-Noise Ratio (SNR) of Dexis intraoral radiographic imaging system improved with higher filtration (Kitagawa and Farman, 2004). Wieder and Adams (1981) showed that aluminum filter can improves resolution of chest radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…Our results corresponded to another authors, as well. Kitagawa and Farman (2004) reported that the Signal-to-Noise Ratio (SNR) of Dexis intraoral radiographic imaging system improved with higher filtration (Kitagawa and Farman, 2004). Wieder and Adams (1981) showed that aluminum filter can improves resolution of chest radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the GC was Al with 1.5 mm in thickness, which differs from other studies. 1,6,7,13,14 Mauriello et al 6 evaluated the effects on image contrast and on exposure dose caused by the increased thickness of the Al filter. In their results was Figure 3 Optical density curves of all filters in the exposure time of 0.32 s and regression analysis of the standard filter including a prediction limit of 5%.…”
Section: Discussionmentioning
confidence: 99%
“…This is why spatial resolution estimates based on picture element size are not able to consistently provide useful information regarding the actual spatial resolution of an imaging system. However, image processing is not the only cause of degradation of image quality; pixel cross-talk, quantum noise, dark current and unequal pixel efficiencies should also be [19][20][21] Within the study, only tests on synthetic images with Gaussian noise were conducted. However, there are numerous types of noise including fixed pattern noise, the type found on digital images acquired by CCD sensors where particular pixels are responsible for creating intensities brighter than the general background noise; and salt and pepper noise, which is typically found in images acquired by sensors containing pixels that have malfunctioned.…”
Section: Discussionmentioning
confidence: 99%